An exploration of symptom burden among breast and gynaecological cancer patients accessing care at University of Ilorin teaching hospital, Ilorin, Kwara State, Nigeria - Isiaka-Lawal, Salamat Ayodele (Department of Public Health and Family Medicine, 2017)
Background: Breast and gynaecological cancers are the leading causes of cancer morbidity and mortality among women in developing countries. Advanced stage diseases with limited availability for treatment imply significant symptom burden; the relief of which poses a challenge for the health care providers. Aim: This study was conducted to measure symptom burden and relief among breast and gynaecological cancer patients accessing care in a tertiary health institution in Nigeria. Objectives : 1)To determine the prevalence of symptoms among breast cancer and gynaecological cancer patients accessing care in UITH, Ilorin; 2) To determine the most distressing symptoms experienced by breast and gynaecological cancer patients accessing care in UITH, Ilorin and 3) To assess symptom relief in the two studied groups. Methods: Both inpatients and outpatients with breast and gynaecologic cancers accessing care during the study period were recruited. All patients completed an interviewer administered MSAS-SF which assesses a 7-day prevalence and distress/frequency of 32 physical/psychological symptoms. Symptom relief was assessed 7 days later. Demographics, cancer stages, treatments received and palliative care referrals were obtained from the case notes. Karnofsky Performance Status Scale was used to assess functional status. Results: Fifty breast and 49 gynaecological cancer patients were studied. Eighty percent of breast cancer and 91.9% of gynaecological cancer patients had advanced cancer. The overall mean number of symptoms was 5.8 ± 4.5 for breast cancer while gynaecological cancers had 8.1 ± 4.6. The top 5 symptoms in breast cancer patients were pain (62%), worrying (44%), feeling sad (42%), weight loss (40%) and difficulty sleeping (38%). Gynaecological cancers had weight loss (67.3%), pain (65.3%), worrying (53.1%), feeling sad (51.0%) and lack of energy (46.9%) as the top 5. The most distressing symptoms were cancer-site specific such as fungating breast masses in breast cancer patients and vaginal bleeding/discharges in gynaecological cancer patients. Both groups similarly had pain and "don't look like myself" as most distressing too. Symptoms reliefs were poor and comparable between the two groups and palliative care referrals were also generally low but worse among breast cancer patients. Gynaecological cancer patients had higher Global Distress Index (GDI= 0.88 Vs 0.48), were more physically distressed (MSAS-PHYS= 0.67 Vs 0.40) and had a poorer KPS (77 ± 17.41 Vs 85 ± 16.91) compared to breast cancer patients. Conclusions: This study shows higher symptom burden in gynaecological cancer patients, a comparably poor symptom relief in both groups and poorer palliative care referrals among breast cancer than the gynaecologic cancer patients. Gynaecological cancer patients had higher symptom prevalence and higher symptom distress scores and lower performance status compared to the breast cancer patients.